2011
DOI: 10.1111/j.1469-7610.2011.02483.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel early intervention for preschool depression: findings from a pilot randomized controlled trial

Abstract: Background Validation for depression in preschool children has been established; however, to date no empirical investigations of interventions for the early onset disorder have been conducted. Based on this and the modest efficacy of available treatments for childhood depression, the need for novel early interventions has been emphasized. Large effect sizes for preschool psychotherapies for several Axis I disorders suggest that earlier intervention in depression may also be promising. Therefore, a novel form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 38 publications
3
91
0
3
Order By: Relevance
“…Therefore, the identification of modifiable environmental exposures that can impact the development of the hippocampus and in turn later emotion functioning is a finding of key public health importance. These findings should inform prevention and early intervention strategies, a number of which have been designed and shown to effectively enhance maternal support (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of modifiable environmental exposures that can impact the development of the hippocampus and in turn later emotion functioning is a finding of key public health importance. These findings should inform prevention and early intervention strategies, a number of which have been designed and shown to effectively enhance maternal support (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…One trial [18] did not assess CBT, instead comparing two other forms of therapy (psychodynamic and family therapy). The other [13] assessed a different form of psychological intervention with a much younger age group (aged 3-7 years). The results of these two studies are described separately.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies [12,13,14] reported results specifically and only for the age group of interest, but in most other studies it was not possible to identify the results specifically for the population of interest (aged 12 and under) from the publications. In these cases we contacted the lead author and/or funder (in the case of the NIH-funded…”
Section: Data Collection Process and Data Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, there are results regarding the effectiveness of this treatment in treating depression disorder. For example, Luby et al [31] used an interactive approach in the treatment of depression in a sample of 54 children aged 3-6 years who lacked metacognitive abilities to use cognitive-behavioral therapy, which had been reported as successful. Also, Lenze et al [32] used interactive therapy successfully with the goal of reducing the symptoms of depression in preschoolers.…”
Section: Conflict Of Interestmentioning
confidence: 99%